An investigation into the isolation performance of mono-and bi-stable systems - Lu, Zeqi; Yang, Tiejun; Brennan, Michael J. [UNESP]; Li, Xinhui; Liu, Zhigang (Springer Nature, 2014)
Motivated by the need for improving the isolation performance, many research studies have been performed on isolators with nonlinear characteristics. Based on the shape of their phase portrait, such devices can be configured as either a mono- or bi-stable isolator. This paper focuses on investigating the relative performance of these two classes under the same excitations. Force transmissibility is used to measure the isolation performance, which is defined in terms of the RMS of the ratio of the transmitted force to the excitation force. When the system is subjected to harmonic excitation, it is found that the maximum reduction of the force transmissibility in the isolation range using Quasi-Zero stiffness is achieved. When the system is subjected to random excitation, it has the same effect of Quasi-Zero stiffness. Further, optimum damping can be changed with stiffness and has minimum value. © 2014 Harbin Engineering University and Springer-Verlag Berlin Heidelberg.
Keywords: bi-stable system; force transmissibility; mono-and bi-stable systems; nonlinear isolation; Quasi-Zero stiffness; random excitation